Towards commercialization of fluorinated cation-disordered rock-salt Li-ion cathodes - Lee, Gi-Hyeok; Lim, Jungwoo; Shin, Jeongyim; Hardwick, Laurence J.; Yang, Wanli (Frontiers in Chemistry, 2023)
Cation-disordered rock-salt cathodes (DRX) are promising materials that could deliver high capacities (>250 mAh g−1) with Earth abundant elements and materials. However, their electrochemical performances, other than the capacity, should be improved to be competitive cathodes, and many strategies have been introduced to enhance DRXs. Fluorination has been shown to inhibit oxygen loss and increase power density. Nevertheless, fluorinated cation-disordered rock-salts still suffer from rapid material deterioration and low scalability which limit their practical applications. This mini-review highlights the key challenges for the commercialization of fluorinated cation-disordered rock-salts, discusses the underlying reasons behind material failure and proposes future development directions.